Change and Continuity in Singapore's Industrial Relations System - PANG, Eng Fong (Institutional Knowledge at Singapore Management University, 1974)
The paper analyses the impact of the two major pieces of legislation enacted by the Singapore Parliament in 1968. It also examines their impact on the industrial relations system and the reaction of the unions and the employees to them. The paper further attempts to identify the forces that are likely to change the system in the near future.